2005
DOI: 10.1111/j.1365-2133.2004.06273.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous manifestations of the malignant carcinoid syndrome

Abstract: This descriptive case series indicates that cutaneous features are not uncommon in the syndrome. They are readily diagnosed on clinical examination, and may be useful indicators of disease activity and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(72 citation statements)
references
References 14 publications
0
68
0
4
Order By: Relevance
“…The presentation will often include a beefy tongue and red skin lesions localized to the face and neck. 6 In addition to the physical symptoms caused by carcinoid tumors and carcinoid syndrome, patients may also suffer from psychiatric complications. Results from two previous studies demonstrated the presence of depressive symptoms in half of patients with carcinoid tumors who had elevated urinary 5-HIAA levels.…”
Section: Discussionmentioning
confidence: 99%
“…The presentation will often include a beefy tongue and red skin lesions localized to the face and neck. 6 In addition to the physical symptoms caused by carcinoid tumors and carcinoid syndrome, patients may also suffer from psychiatric complications. Results from two previous studies demonstrated the presence of depressive symptoms in half of patients with carcinoid tumors who had elevated urinary 5-HIAA levels.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of pellagra in serotonin-producing NET patients is about 5% [12] and especially reveals during the advanced stage of the disease [10]. Niacin deficiency might be underestimated in patients with a serotonin-producing NET.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with serotonin-producing NETs, pellagra and other symptoms suggestive of tryptophan and/or niacin deficiency are reported [3,4,10,11,12]. Niacin supplementation resulted in a quick and substantial improvement in the symptoms of these patients [4,11].…”
Section: Introductionmentioning
confidence: 99%
“…En effet, des cas de carcinome é pidermoïde ont é té dé crits chez des patients ayant une morphé e gé né ralisé e. Cette association ne semble pas ê tre fortuite é tant donné la rareté des morphé es gé né ralisé es et l'utilisation fré quente de la Puvathé rapie dans le traitement de ces sclé rodermies [14,16,17] ; -on peut observer une association entre morphé e et certains cancers, particuliè rement les cancers colorectaux [6,8], tel est le cas de notre observation, le cancer du sein [9] et les syndromes carcinoïdes [1] ; -la morphé e peut survenir dans des zones qui sont irradié es chez des patients ayant dé jà un cancer, notamment du sein [2] ; -quelques cas de morphé e induite par des traitements chimiothé rapiques pour un cancer ont é té dé crits [7] ; -enfin, aspect sclé rodermiforme que peuvent prendre des mé tastases cutané es de certains cancers, notamment le cancer de la prostate [13].…”
Section: Commentairesunclassified